Enhancing the position estimates of unmanned aerial vehicles by cooperation. Issue 3 (19th August 2014) - Hlavacs, Helmut
Abstract : Purpose: The aim of the research is to find methods to enhance position estimates for mobile terminals by cooperating with each other. Design/methodology/approach: The main methods used are on the one hand mathematical modelling of the system, drone mobility, communication and positioning errors, and on the other hand detailed discrete event simulation, which we use to evaluate the positioning errors. In the simulation runs, we vary important parameters like signal speed, terminal velocity, area size, or error correlation. We detail the influence of these parameters on the theoretically possible error enhancement with respect to the traditional non-cooperative method. Findings: Simulation results show that using cooperation is useful and can indeed significantly enhance the accuracy of position estimates, even in difficult situations. However, there are limits and the accuracy cannot always be enhanced Research limitations/implications: Future research might use more sophisticated processing methods to further enhance position estimates. Limitations are given by the use of discrete time models in an inherently continuous system. Discretization errors are however kept low by using small time steps. Practical implications: We have shown that the positioning of drone swarms can be significantly enhanced once drones cooperate with each other. This might improve maneuverability of drones in all situations where drone swarms are used. Originality/value: We have proven by using simulation that cooperative positioning can yield positioning enhancements, even in difficult situations, when using wireless communication. In this light, future research can come up with practical implementations of such cooperative approach.